You are on page 1of 15

Exercise 6.

1 (Solutions)

MathCity.org

Available online @ http://www.mathcity.org, Version: 2.0.0

Page # 255

Circle
The set of all point in the plane that are equally distant from a fixed point is called a
circle.
The fixed point is called centre of the circle and the distance from the centre of the
circle to any point on the circle is called the radius of circle.
Equation of Circle
Let r be radius and C ( h, k ) be centre of circle. Let P ( x, y )
be any point on circle then
P(x,y)
PC = r
r
( x h) 2 + ( y k ) 2 = r
C(h,k)
On squaring
2
2
( x h) + ( y k ) = r2
This is equation of circle in standard form.
If centre of circle is at origin i.e. C ( h, k ) = C ( 0,0 ) then equation of circle becomes
x2 + y2 = r 2

Equation of circle with end points of diameter

Let A ( x1 , y1 ) and B ( x2 , y2 ) be end points of
diameter.
Let P ( x, y ) be any point on circle then
mAPB = 90
(Note: An angle in a semi circle is a right
angle see Theorem 4 at page 270)
Thus the line AP and BP are ar to each other
and we have
(Slope of AP ) (Slope of BP ) = 1
y y1 y y2

= 1
x x1 x x2

A(x1 ,y1)

P(x ,y)

B(x2 ,y2)

( y y1 )( y y2 ) = ( x x1 )( x x2 )
( x x1 )( x x2 ) + ( y y1 )( y y2 ) = 0

General form of an equation of a circle

The equation
x 2 + y 2 + 2 gx + 2 fy + c = 0
represents a circle.
2
2
2
x + 2 gx + g + y + 2 fy + f 2 + c = g 2 + f 2

(x + g)

+(y+ f )

= g2 + f 2 c

( x ( g ) )

+ ( y ( f ) )

g + f c

This is equation of circle in standard form with

centre at ( g , f ) and radius = g 2 + f 2 c

Question # 1(a)
Given: centre C ( h, k ) = ( 5, 2 )
Equation of circle:
2
2
( x h) + ( y k ) = r2

( x 5)

+ ( y + 2)

( 4)

x 2 10 x + 25 + y 2 + 4 y + 4 = 16
x 2 + y 2 10 x + 4 y + 25 + 4 16 = 0
x 2 + y 2 10 x + 4 y + 13 = 0

Question # 1(b)
Given:

centre C ( h, k ) =

2, 3 3

radius = r = 2 2

Equation of circle:
2
2
( x h) + ( y k ) = r2

(x 2 ) + ( y + 3 3)

(2 2 )

x 2 2 2 x + 2 + y 2 + 6 3 y + 27 = 8
x 2 + y 2 2 2 x + 6 3 y + 2 + 27 8 = 0
x 2 + y 2 2 2 x + 6 3 y + 21 = 0

Question # 1(c)
Given end points of diameter:
A ( x1 , y1 ) = ( 3,2 ) , B ( x2 , y2 ) = ( 5, 6 )
Equation of circle with ends of diameter is
( x x1 )( x x2 ) + ( y y1 )( y y2 ) = 0
( x (3) )( x 5 ) + ( y 2 )( y (6) ) = 0
( x + 3)( x 5 ) + ( y 2 )( y + 6 ) = 0
x 2 + 3 x 4 x 15 + y 2 2 y + 6 y 12 = 0
x 2 + y 2 2 x + 4 y 27 = 0

Question # 2(a)
x 2 + y 2 + 12 x 10 y = 0
Here 2 g = 12 , 2 f = 10 , c = 0
g =6 ,
f = 5
So centre = ( g , f ) = ( 6,5 )
www.MathCity.org

FSC-II / Ex. 6.1 - 3

g2 + f 2 c

(6) 2 + (5) 2 0

36 + 25

61

Question # 2(b)
5 x 2 + 5 y 2 + 14 x + 12 y 10 = 0
14
12
x2 + y 2 + x + y 2 = 0
5
5
14
12
Here 2 g =
, 2f =
, c = 2
5
5
7
6
g=
,
f =
5
5
7 6
Centre = ( g , f ) = ,
5 5
2

g + f c

ing by 5

7 6
5 + 5 (2)

49 36
27
+
+2 =
25 25
5

= 3

3
5

Question # 2(c) & (d)

Do yourself as above.

Question # 3
Given: A ( 4,5 ) , B ( 4, 3) , C ( 8, 3)
Let H ( h, k ) be centre and r be radius of circle, then
AH

AH

=
2

BH
BH

CH

=
2

CH

A
B
r

= r
2

r
C

= r2

( h 4 ) + ( k 5 ) = ( h + 4 ) + ( k + 3) = ( h 8 ) + ( k + 3) = r 2 (i)
From eq. (i)
2
2
2
2
( h 4 ) + ( k 5 ) = ( h + 4 ) + ( k + 3)
h 2 8h + 16 + k 2 10k + 25 = h 2 + 8h + 16 + k 2 + 6k + 9
h 2 8h + 16 + k 2 10k + 25 h 2 8h 16 k 2 6k 9 = 0
16h 16k + 16 = 0
h + k 1 = 0 . (ii)
Again from (i )
2

( h + 4 ) + ( k + 3) = ( h 8 )
2
2
( h + 4 ) = ( h 8)

+ ( k + 3)

h 2 + 8h + 16 = h 2 16h + 64
h 2 + 8h + 16 h 2 + 16h 64 = 0
24h 48 = 0

24h = 48

h = 2

www.MathCity.org

Putting value of h in (ii)

2 + k 1 = 0

k +1 = 0

k = 1

Again from (i )
2

r2 =

( h 4 ) + ( k 5)
2
2
= ( 2 4 ) + ( 1 5 )
h=2,
2
2
= ( 2 ) + ( 6 ) = 4 + 36 = 40
Now equation of circle with centre at H ( 2, 1) & r =
2
2
2
( x 2 ) + ( y + 1) = ( 40 )

k = 1

r =

40

40

x 2 4 x + 4 + y 2 + 2 y + 1 = 40
x 2 + y 2 4 x + 2 y + 4 + 1 40 = 0
x 2 + y 2 4 x + 2 y 35 = 0

Ans.

Question # 3(b)
Given: A ( 7,7 ) , B ( 5, 1) , C (10,0 )
Let H ( h, k ) be centre and r be radius of circle, then
AH

AH

BH

=
2

BH

CH

=
2

CH

A
B
r

= r
2

r
C

= r2
2

( h + 7 ) + ( k 7 ) = ( h 5 ) + ( k + 1) = ( h 10 ) + ( k 0 ) = r 2 . (i)
From equation (i) we have
2
2
2
2
( h + 7 ) + ( k 7 ) = ( h 10 ) + ( k 0 )
h 2 + 14h + 49 + k 2 14k + 49 = h 2 20h + 100 + k 2
h 2 + 14h + 49 + k 2 14k + 49 h 2 + 20h 100 k 2 = 0
34h 14k 2 = 0 17 h 7 k 1 = 0 . (ii)
Again from (i )

( h 5)

+ ( k + 1)

( h 10 )

+ ( k 0)

h 2 10h + 25 + k 2 + 2k + 1 = h 2 20h + 100 + k 2

h 2 10h + 25 + k 2 + 2k + 1 h 2 + 20h 100 k 2 = 0
10h + 2k 74 = 0
5h + k 37 = 0 . (iii)
Multiplying eq. (iii) by 7 and subtracting from (ii)
17 h 7 k 1 = 0
35h + 7 k 259 = 0

52h

260 = 0

52h = 260

h = 5

www.MathCity.org

FSC-II / Ex. 6.1 - 5

5 ( 5 ) + k 37 = 0 25 + k 37 = 0 k 12 = 0

k = 12

Again from eq. (i), we have

2
2
r2 = (h + 7) + (k 7)
2

= ( 5 + 7 ) + (12 7 ) = (12 ) + ( 5 ) = 144 + 25 = 169

r = 13
Now equation of circle with centre ( 5,12 ) and radius 13 :

( x 5)

+ ( y 12 )

= (13) 2

x 2 10 x + 25 + y 2 24 y + 144 = 169
x 2 + y 2 10 x 24 y + 25 + 144 169 = 0
x 2 + y 2 10 x 24 y = 0

is required equation.

Question # 3(c)
Given: A ( a,0 ) , B ( 0, b ) , C ( 0,0 )
Let H ( h, k ) be centre and r be radius of circle, then
AH

AH

BH

=
2

BH

CH

=
2

B
r

r
r

= r

CH

= r2

( h a ) + ( k 0) = ( h 0) + ( k b ) = ( h 0) + ( k 0) = r 2
2
2
( h a ) + k 2 = h 2 + ( k b ) = h 2 + k 2 = r 2 .. (i)

From equation (i)

2
( h a ) + k 2 = h2 + k 2
h 2 2ha + a 2 + k 2 = h 2 + k 2
2ha + a

2ha = a

= 0

a2
h =
2a

h=

a
2

Again from equation (i)

2
h2 + ( k b ) = h2 + k 2
h 2 + k 2 2bk + b 2 = h 2 + k 2
2bk = b 2

k =

b2
2b

2bk + b 2 = 0

k =

b
2

Again from equation (i)

r 2 = h2 + k 2
2

a b
= +
2 2

a 2 b2
=
+
4
4

r =

a b
Now equation of circle with centre , and radius
2 2

a2 b2
+
4
4
a2 + b2
2

www.MathCity.org

FSC-II / Ex. 6.1 - 6

2

a
b

+
y

2
2

a2
b2
x 2 ax + + y 2 by +
4
4
2
a
b2
2
2
x ax + + y by +
4
4
2
2
x + y ax by = 0

a 2 b2
+
4
4

a2 b2
=
+
4
4
2
2
a b

= 0
4
4

Alternative Method
Given point on circle: A ( a,0 ) , B ( 0, b ) , C ( 0,0 )
Consider an equation of circle in standard form
x 2 + y 2 + 2 gx + 2 fy + c = 0 . (i)
Since A ( a,0 ) lies on circle, therefore
(a ) 2 + (0)2 + 2 g (a ) + 2 f (0) + c = 0
a 2 + 2 ga + c = 0 . (ii)
Also B ( 0, b ) lies on the circle, then
(0) 2 + (b) 2 + 2 g (0) + 2 f (b) + c = 0
b 2 + 2 fb + c = 0 . (iii)
Also C ( 0,0 ) lies on the circle, therefore
c = 0

(0) 2 + (0) 2 + 2 g (0) + 2 f (0) + c = 0

Putting value of c in (ii )
2

a + 2 ga + 0 = 0

2ga = a

a2
g =
2a

g =

a
2

Putting value of c in (iii )

b 2 + 2 fb + 0 = 0

2 fb = b 2

b2
b
f =
2b
2
Putting value of g , f and c in (i)
a
b
x2 + y2 + 2 x + 2 y + 0 = 0
2
2
f =

x 2 + y 2 ax by = 0
is required equation of circle.

Question # 4(a)
Given: A ( 3, 1) , B ( 0,1)
l : 4x 3y 3 = 0
Let C ( h, k ) be centre and r be radius of circle
A & B lies on circle
CA = CB = r

B
A
l
C(h,k)

www.MathCity.org

FSC-II / Ex. 6.1 - 7

( h 3) + ( k + 1) = ( h 0 ) + ( k 1)
2
2
2
( h 3) + ( k + 1) = h 2 + ( k 1)

= r .. (i)
on squaring

h 6h + 9 + k + 2 k + 1 = h + k 2k + 1
2

h 2 6h + 9 + k 2 + 2k + 1 h 2 k 2 + 2 k 1 = 0
6h + 4k + 9 = 0 (ii)
Now since C ( h, k ) lies on given equation l
4h 3k 3 = 0 (iii)
ing equation (ii) by 3 & (iii) by 4 then adding
18h + 12k + 27 = 0
16h 12 k 12 = 0
2h

+ 15 = 0

2h = 15

h =

15
2

Putting in (iii)
15
4 3k 3 = 0
30 3k 3 = 0
2
3k + 27 = 0 3k = 27 k = 9
Now from eq. (i)
r =

h 2 + ( k 1)

2
15
2 + ( 9 1)

225
+ 64
4

448
4

15
Now equation of circle with centre at C ( h, k ) = ,9 and radius
2

481
4

2
481
15
2

+
y

9
=
(
)
4

225
481
x 2 15 x +
+ y 2 18 y + 81
= 0
4
4
x 2 + y 2 15 x 18 y + 17 = 0

r = AC

A(-3,1)
l

r =2

Question # 4(b)
Given: A ( 3,1) lies on circle , radius = r = 2
l : 2x 3y + 3 = 0
Let C ( h, k ) be centre of circle.
Since A ( 3,1) lies on circle

C(h,k)

www.MathCity.org

FSC-II / Ex. 6.1 - 8

2 =
4 =

( h + 3) + ( k 1)
2
2
( h + 3) + ( k 1)

4 = h 2 + 6h + 9 + k 2 2k + 1
h 2 + 6h + 9 + k 2 2k + 1 4 = 0
h 2 + 6h + 9 + k 2 2k 3 = 0 .. (i )
Since centre C ( h, k ) lies on l
2h 3k + 3 = 0
3k 3
2h = 3k 3 h =
. (ii )
2
Putting value of h in (i )
2

3k 3
3k 3
2
2 + k + 6 2 2k + 6 = 0

9k 2 18k + 9

+ k 2 + 9k 9 2k + 6 = 0
4
9k 2 18k + 9 + 4k 2 + 36k 36 8k + 24 = 0

ing by 4

13k 2 + 10k 3 = 0 13k 2 + 13k 3k 3 = 0

13k ( k + 1) 3 ( k + 1) = 0

( k + 1)(13k 3)

k = 1

= 0

or

k =

3
13

Putting value of k in (ii)

3(1) 3
h =
2
6
=
2
= 3
( 3, 1) is centre of circle

h =

3 ( 313) 3
2
9 3
30
13
13 = 15
=
=

2
2
13
15 3
, is centre of circle.
13 13

Now equation of circle with centre at ( 3,1) and radius 2

( x + 3)

+ ( y + 1) = (2)2

( x + 3)

+ ( y + 1) = 4

15 3
Now equation of circle with centre at , and radius 2
13 13
2
2
15
3

2
x + 13 + y 13 = (2)

15
3

x+ +y = 4
13
13

www.MathCity.org

FSC-II / Ex. 6.1 - 9

Question # 4(c)
Given: A ( 5,1) and l : 2 x y 10 = 0 is tangent at B ( 3, 4 )
Let C ( h, k ) be centre and r be radius of circle.
A ( 5,1) and B ( 3, 4 ) lies on circle
AC = BC = r

( h 5) + ( k 1) = ( h 3) + ( k + 4 )
2
2
2
2
( h 5) + ( k 1) = ( h 3) + ( k + 4 )

l
B

4)
(3,-

A(5,1)
r
C(h,k)

= r ..... (i)
On squaring

h 2 10h + 25 + k 2 2k + 1 = h 2 6h + 9 + k 2 + 8k + 16
h 2 10h + 25 + k 2 2k + 1 h 2 + 6h 9 k 2 8k 16 = 0
4h 10k + 1 = 0 .. (ii)
a
2
=
= 2
Now slope of tangent l = m1 =
b
1
k +4
And slope of radial segment CB = m2 =
h3
Since radial segment is perpendicular to tangent therefore
m1m2 = 1
k +4
2
= 1 2k + 8 = h + 3
h3
h 3 + 2k + 8 = 0
h + 2k + 5 = 0 .. (iii)
Multiplying eq. (iii) by 4 and adding in (ii)
4h + 8k + 20 = 0
4h 10 k + 1 = 0
2k

+ 21 = 0

2k = 21

k =

21
2

Putting value of k in (iii)

21
h + 2 + 5 = 0 h + 21 + 5 = 0
2
h + 26 = 0 h = 26
Now from eq. (i)
r =

( h 3)

+ ( k + 4)

2
2

=
=

21
( 26 3) + 2 + 4

841
4205
841 +
=
4
4
2

29
( 29 ) + 2

21

2

4205
4
www.MathCity.org

FSC-II / Ex. 6.1 - 10

2

2
4205
21

( x + 26 ) + y 2 = 4

441 4205
x 2 + 52 x + 676 + y 2 21 y +

= 0
4
4
x 2 + y 2 + 52 x 21y 265 = 0
2

Question # 4(d)
Given; A (1, 4 ) , B ( 1,8 )
l : x + 3y 3 = 0
Let C ( h, k ) be centre and r be radius of circle then
AC = BC = r
2

( h 1) + ( k 4 ) = ( h + 1) + ( k 8 ) = r . (i)
Also l is tangent to circle
radius of circle = ar distance of C ( h, k ) form l
r =

h + 3k 3

r =

h + 3k 3

(1) 2 + (3)2

10

. (ii)

Now from (i)

( h 1)

+ ( k 4) =

( h + 1)

+ ( k 8)

On squaring

( h 1)

+ ( k 4 ) = ( h + 1) + ( k 8 )

h 2 2h + 1 + k 2 8k + 16 = h 2 + 2h + 1 + k 2 16k + 64
h 2 2h + 1 + k 2 8k + 16 h 2 2h 1 k 2 + 16k 64 = 0
4h + 8k 48 = 0
h 2k + 12 = 0 . (iii)
Now from (i) & (ii)
h + 3k 3
2
2
( h 1) + ( k 4 ) =
10
On squaring
2
h + 3k 3
2
2
( h 1) + ( k 4 ) =
10
2
2
10 ( h 1) + ( k 4 ) = h 2 + 9k 2 + 9 + 6hk 18k 6h

2
2
10 h 2h + 1 + k 8k + 16 = h 2 + 9k 2 + 9 + 6hk 18k 6h

10h 2 20h + 10 + 10k 2 80k + 160 h 2 9k 2 9 6hk + 18k + 6h = 0

9h 2 + k 2 14h 62k 6hk + 161 = 0 . (iv)
www.MathCity.org

FSC-II / Ex. 6.1 - 11

From (iii)
h = 2k 12 .. (v)
Putting in (iv)
2
9 ( 2k 12 ) + k 2 14 ( 2k 12 ) 62k 6 ( 2k 12 ) k + 161 = 0

36k 2 432k + 1296 + k 2 28k + 168 62k 12k 2 + 72k + 161 = 0

25k 2 450k + 1625 = 0
k 2 18k + 65 = 0

ing by 25

k ( k 13) 5 ( k 13) = 0

k 2 13k 5k + 65 = 0

( k 13)( k 5 ) = 0
k = 13 or k = 5
Putting in eq. (v)
h = 2(13) 12
= 26 12 = 14
Now from (i)
2

r =

( h 1)

r =

(14 1)

(13)

+ ( k 4)

Putting in (v)
h = 2 ( 5 ) 12
= 10 12 = 2
Now from (i )

+ (13 4 )

+ (9)

169 + 81

( x 14 )

+ ( y 13) =

+ (5 4)

( 2 1)

250

= 1+1 = 2
Now eq. of circle with centre ( 2,5 )

2

+ ( k 4)

( h 1)

= 250
Now eq. of circle with centre (14,13)

( x 14 )

r =

2
2

( 2)

( x 2)

+ ( y 5) =

( x 2)

+ ( y 5) = 2

+ ( y 13) = 250

Question # 5
Radius of circle = r = a
circle lies in second quadrant and touching both the
axis therefore centre of circle is ( a, a )
So equation of circle
2
2
( x (a ) ) + ( y a ) = (a) 2

( a,a) a
a
x

x + 2ax + a + y 2ay + a a = 0
x 2 + y 2 + 2ax + 2ay + a 2 = 0
2

www.MathCity.org

FSC-II / Ex. 6.1 - 12

Question # 6
Suppose
l1 : 3 x 2 y = 0
l2 : 2 x + 3 y 13 = 0

l1

S : x2 + y2 + 6x 4 y = 0
From S
2g = 6 , 2 f = 4 , c = 0
g = 3 ,
f = 2 ,
Centre C ( g , f ) = C ( 3, 2 )

C( 3,2)

g2 + f 2 c
(3) 2 + (2) 2 0

= 9 + 4 = 0 = 13
Now to check l1 is tangent to circle, we find
3(3) 2(2) + 0
ar distance of l1 from centre =
(3) 2 + (2) 2
94
13
13
=
=
=
9+4
13
13
= 13 = radius of circle
l1 is tangent to given circle.
Now to check l2 is tangent to circle, let
2(3) + 3(2) 13
ar distance of l2 from centre =
(2) 2 + (3) 2
=
=

6 + 6 13
4+9
13
13

13
13

= 13 = Radius of circle

Circles touching each other externally or

internally
Let C1 be centre and r1 be radius of circle S1 and C2 be
centre and r2 be radius of circle S2 .
Then they touch each other externally if
C1C2 = r1 + r2

r1

r2

C1

C2

S1
S2

r1 C1 C2

C1C2 = r2 r1

r2

www.MathCity.org

FSC-II / Ex. 6.1 - 13

Question # 7
Let S1 : x 2 + y 2 + 2 x 2 y 7 = 0
S2 : x 2 + y 2 6 x + 4 y + 9 = 0
For S1 :
2 g = 2 , 2 f = 2 , c = 7
g =1 ,
f = 1 ,
Let C1 be centre and r1 be radius of circle S1 , then
C1 ( g , f ) = C1 ( 1,1)

r1

r2

C1

C2

S1
S2

g2 + f 2 c

(1) 2 + (1)2 (7) =

1+1+ 7

9 = 3

For S2 :
2 g = 6 , 2 f = 4 , c = 9
g = 3 ,
f =2
Let C2 be centre and r2 be radius of circle S2 then
C2 ( g , f ) = C2 ( 3, 2 )

g2 + f 2 c

= (3) 2 + (2) 2 9 =
Now circles touch each other externally if
C1C2 = r1 + r2

(3 + 1) 2 + (2 1) 2 = 3 + 2

16 + 9 = 5

9+ 49

4 = 2

25 = 5
5 = 5
Hence both circles touch each other externally.

Question # 8
Suppose S1 : x 2 + y 2 + 2 x 8 = 0
S2 : x 2 + y 2 6 x + 6 y 46 = 0
For S1 :
2 g = 2 , 2 f = 0 , c = 8
g =1 ,
f =0
Let C1 be centre and r1 be radius of circle S1 then
C1 ( g , f ) = C ( 1,0 )
=

r 1 C1 C2

r2

g2 + f 2 c
(1) 2 + (0)2 + 8

= 3

For S2 :
2 g = 6 ,

2f =6 ,

c = 46
www.MathCity.org

FSC-II / Ex. 6.1 - 14

g = 3 ,
f =3
Let C2 be centre and r2 be radius of circle S2 then
C2 ( g , f ) = C2 ( 3, 3)

g2 + f 2 c

= (3)2 + (3)2 (46) =

Now circles touch each other internally if
C1C2 = r2 r1

9 + 9 + 46

64

=8

(3 + 1)2 + (3 0) 2 = 8 3

16 + 9 = 5
25 = 5 5 = 5
Hence circles are touching each other internally.

Question # 9
Given: Radius r = 2 ,
Tangent: x y 4 = 0 at A (1, 3)
Suppose C ( h, k ) be the centre then
AC = 2
2

( h 1) + ( k + 3) = 2
On squaring
2
2
( h 1) + ( k + 3) = 4

,-3)
A(1

ent
tang

2
C(h,k)

h 2 2h + 1 + k 2 + 6 k + 9 4 = 0
h 2 + k 2 2h + 6k + 6 = 0 .. (i)
k +3
Now slope of radial line AC =
h 1
1
Slope of line tangent =
=1
1
Since radial line is ar to tangent, therefore
(Slope of radial line) (Slope of tangent) = 1
k +3

(1) = 1

h
1

k + 3 = ( h 1) k = h + 1 3
k = h 2 .. (ii)
Putting in (i)
2
h 2 + ( h 2 ) 2h + 6 ( h 2 ) + 6 = 0
h 2 + h 2 + 4h + 4 2h 6h 12 + 6 = 0
2 h 2 4h 2 = 0

h 2 2h 1 = 0

www.MathCity.org

FSC-II / Ex. 6.1 - 15

2 (2)2 4(1)(1)
h =
2(1)
2 4+4
2 8
=
2
2
22 2
=
= 1 2
2
=

k = 1 2 2

Putting h = 1 2 in (ii)
k = 1+ 2 2

k = 3 2
Now equation of circle with

k = 3+ 2
Now equation of circle with

Putting h = 1 + 2 in (ii )

x 1

Book:

) (
2) ( y + 3+

x (1 + 2)

y (3 2)
2)

centre 1 2, 3 + 2 and radius 2.

2

= (2) 2

( x (1 2) ) ( y (3 + 2) )
( x 1 + 2 ) ( y + 3 2) )
2

= 4

= (2) 2
= 4

Exercise 6.1 (Page 255)

Calculus and Analytic Geometry Mathematic 12
Punjab Textbook Board, Lahore.
Edition: May 2013.
Made by: Atiq ur Rehman (Atiq@MathCity.org)
Available online at http://www.MathCity.org in PDF Format
(Picture format to view online).
Page Setup used A4.
Updated: April 03, 2015.

Error Analyst
Waiting for someone

www.MathCity.org